(untitled) (Jurnal Manajemen dan Organisasi, 2019)
By virtue of international agreements, Association of South East Asia Nation (ASEAN) member countries are currently in an economic cooperation within the ASEAN community. Potatoes are a leading commodity in Indonesia’s agricultural sector, due to high production but only succeeded in exporting to two ASEAN countries and still inferior to Malaysia and Singapore. This study aims to identify competitiveness of the potato as a commodity, using Internal Factor Evaluation (IFE), using External factor evaluation (EFE) matrix and analyze the position of Indonesian potatoes using the Internal-External (IE) matrix. The analytical tools used in this study are EFE matrix, IFE matrix, and IE matrix. The sampling technique was purposive sampling, using the assessment of experts or experts who mastered the agricultural field, especially increasing the competitiveness of potato commodities, which knew potato farming from upstream to downstream. The results of this study indicate that internally and externally Indonesia is strong enough in facing the ASEAN Economic Community (AEC), currently in a condition of hold and maintain, a strategy that can be done to strengthen the Indonesian potatoes internally and externally is to market penetration and product development.